Memperluas Penelitian Psikologi: Dari Masyarakat WEIRD Menuju Inklusivitas Global - Abraham, Juneman; Siaputra, Ide Bagus (ANIMA Indonesian Psychological Journal, 2025)
The dominance of WEIRD (Western, Educated, Industrialized, Rich, and Democratic) countries in global psychology research limits the diversity of perspectives. This affects the indexing and global exposure of psychology research from countries outside these categories, one of which is Indonesia. ANIMA Indonesian Psychological Journal, as one of the Indonesian psychology journals committed to international standards, has taken a number of steps to increase global access to Indonesian psychology, with the ultimate goal of realizing a more inclusive psychology. These steps are explained in more detail in this editorial article.